2011
DOI: 10.2337/db11-0571
|View full text |Cite
|
Sign up to set email alerts
|

Control of Blood Glucose in the Absence of Hepatic Glucose Production During Prolonged Fasting in Mice

Abstract: OBJECTIVESince the pioneering work of Claude Bernard, the scientific community has considered the liver to be the major source of endogenous glucose production in all postabsorptive situations. Nevertheless, the kidneys and intestine can also produce glucose in blood, particularly during fasting and under protein feeding. The aim of this study was to better define the importance of the three gluconeogenic organs in glucose homeostasis.RESEARCH DESIGN AND METHODSWe investigated blood glucose regulation during f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 46 publications
5
117
1
1
Order By: Relevance
“…The rise in EGP offsets in part the glucose lost through the urine, thereby blunting the expected decline in glycaemia. The increased EGP can be attributed, at least in part, to the lower insulin and glucose and higher glucagon levels, but other mechanisms cannot be ruled out [22].…”
Section: Introductionmentioning
confidence: 99%
“…The rise in EGP offsets in part the glucose lost through the urine, thereby blunting the expected decline in glycaemia. The increased EGP can be attributed, at least in part, to the lower insulin and glucose and higher glucagon levels, but other mechanisms cannot be ruled out [22].…”
Section: Introductionmentioning
confidence: 99%
“…The transcription factors and coactivators involved in the control of gluconeogenesis have been studied by several authors and confirmed by chromatin immunoprecipitation assay. [32][33][34][35][36] FoxO1 is also known to inhibit the mRNA expression of CYP7A1. 37 Consistently, CYP7b1 expression is dramatically decreased in the liver of obB2KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of blood glucose and serum insulin were measured using a Glucometer Elite monitor or Mercodia Ultrasensitive Rat Insulin ELISA kit (ALPCO Diagnostics, Salem, NH), respectively. An L-alanine tolerance test was performed by intraperitoneal injection of 2 g/kg L-alanine after 24-h fasting as described previously (20). Glucose tolerance tests (GTTs) and insulin tolerance tests (ITTs) were performed by intraperitoneal injection of 2 g/kg glucose after overnight fasting and 0.75 units/kg insulin after 4-h fasting, respectively.…”
Section: Luciferase Assaymentioning
confidence: 99%